2020
DOI: 10.1111/jphp.13186
|View full text |Cite
|
Sign up to set email alerts
|

Development of an on-line Raman spectral analytical method for monitoring and endpoint determination of the Cornu Caprae Hircus hydrolysis process

Abstract: Objectives Cornu Caprae Hircus (goat horn, GH), a medicinal animal horn, is frequently used in traditional Chinese medicine, and hydrolysis is one of the most important processes for GH pretreatment in pharmaceutical manufacturing. In this study, on‐line Raman spectroscopy was applied to monitor the GH hydrolysis process by the development of partial least squares (PLS) calibration models for different groups of amino acids. Methods Three steps were considered in model development. In the first step, design of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 62 publications
(78 reference statements)
0
8
0
Order By: Relevance
“…Raman spectroscopy is highly suitable for the application in aqueous systems since the Raman signal of water is not as dominant as that found with other techniques such as infrared (IR) spectroscopy (Webster et al, 2018; Yan et al, 2020). Unlike fluorescence spectroscopy, Raman spectroscopy is not limited to fluorescent molecules (Bockisch et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Raman spectroscopy is highly suitable for the application in aqueous systems since the Raman signal of water is not as dominant as that found with other techniques such as infrared (IR) spectroscopy (Webster et al, 2018; Yan et al, 2020). Unlike fluorescence spectroscopy, Raman spectroscopy is not limited to fluorescent molecules (Bockisch et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Unlike fluorescence spectroscopy, Raman spectroscopy is not limited to fluorescent molecules (Bockisch et al, 2019). It can be applied in‐situ, non‐destructively, and non‐invasively while showing high specificity because of its “detailed molecular fingerprint” (Yan et al, 2020). Therefore, Raman spectroscopy is an appropriate PAT tool for simultaneous monitoring of several process parameters of a bioprocess (Hirsch et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The existing Cl in liquid CP is a typical secondary chloride with both S HH and S HC conformations based on Mizushima’s notation, representing the C–Cl stretching mode of the CH–Cl units in syndiotactic and isotactic sequences, respectively. The investigation of chlorinated polyethylenes showed that chlorination can affect the structure and conformation of CPs, which, in turn, can be used for the quantitative determination of Cl contents in CPs by the corresponding vibrational frequencies with specific conformations. , In addition to the rapid and nondestructive data acquisition process, Raman spectroscopy has great potential for the online monitoring of chemical productions. …”
Section: Introductionmentioning
confidence: 99%